Consumer and Customer Engagement: A Review of The Decade (2010-2019) and Future Directions - Santos, Sylvio Ribeiro de Oliveira; Oliveira, Daniel Max de Sousa (Revista Ciências Administrativas, 2023)
Customer engagement has been a marketing research priority throughout the decade and several frameworks have tried to conceptualize the phenomenon. Thus, this article aims to summarize ten years of theoretical and empirical studies on customer engagement and to propose directions for future studies about it. A broad review of articles on customer, consumer and brand engagement was conducted and discussed, aiming at the convergence between different existing perspectives. As one of its contributions,this article argues for a more social and dynamic concept of engagement, suggesting the use of the term “consumer engagement”, because the engagement value for the brand comes not just from customers, but from anyone who has contact with the brand, for example through social media.